Determining the moment and form of concluding a passenger transport contract based on the judgment of the Court of Justice of the European Union in joined cases C-349/18 to C-351/18 - Karol Lange (Przegląd Komunikacyjny)
The article focuses on discussing the norms of Polish transport law and European Union regulations on the correctly defined of the moment and form of concluding a contract of passengers transport in railway systems. The article also describes the problem of discourse between the content of these legal norms and the jurisprudence practice and doctrine opinion. Moreover, was performed to present a comparative analysis of the relation of the Court of justice of the European Union judgment to the norms of Polish and European law and the case law. Commented on the practices of carriers in regulating the said matter. Internal law acts applicable to the means of transport of Polish railway companies were also analyzed. Keywords: Transport law; Contract of passenger transport; European Union law; Railway transport